A Survey on Dentistry Students Satisfaction with their Discipline and Some of the Related Factors - Zahra Fattahi; Yadolah Javadi; Nozar Nakhaee (Kerman University of Medical Sciences, 2004)
Background: Dental and oral diseases are among the most important health problems of the country Therefore the training of dutiful interested and skilled dentists is one of the educational priorities of Ministry of Health Treatment and Medical Education Attention to the quality of training programs related to the community health services is of a great importance Objective: To evaluate Kerman dentistry students satisfaction with their discipline Methods: This descriptive - cross sectional study was performed on dentistry students of Kerman Dentistry School In order to gather data a researcher - made questionnaire was used Data analysis was done through MannWhitney U test and Spearmans correlation coefficient Results: In this study 557% of subjects were male and the rest were female From all subjects 743% showed a great interest 171 a moderate interest and the rest little interest in their field of study In regard to discipline satisfaction 86% intended to quit their study while 757% showed complete satisfaction The most effective reasons of discipline satisfaction were "the possibility of giving service to people" (76%) "good social statue" (657%) and "being interested in discipline" (656%) Conclusion: The majority of subjects were satisfied with their discipline and showed an increasing interest As one of the important educational factors is being interested and satisfied with disciplin this point should be considered as a priority in the planning of educational programs